(untitled) (Journal of Philosophy, Culture and Political Science, 2021)
The ransom dilemma problem all around the world raises not only moral concerns for the government, but also for the society as a whole in whether to save the kidnapped person or to do nothing against it. While the U.S. and U.K. deal with this according to its strict laws and regulations ruthlessly in order to preserve the integrity of the society, the European Union deals it with a more flexible and is oriented toward a human-centered approach. This paper will try to analyze this ethical dilemma from three diverging viewpoints. These concern the consequentialist/utilitarian viewpoints and the deontological approach. While consequentialists support the argument that states ought to preserve the security of their citizens without giving in to the demands of terrorists for an exchange of the kidnapped person, deontologists on the other hand put human values and individual rights to the forefront and urges states to save people no matter what the circumstances they are in. Here, we will refer to the arguments presented by ethicists such as Jeremy Bentham or John Stuart Mill as well as experts like Peter Singer. However, in terms of deontological approach it comes with caveats in arguments between Kantian absolutism approach in categorical impetrative beliefs and Rossian intuitive prima facie duties approach. This paper serves the purpose of informing and enlightening readers on the ethical issues that ransom dilemma presents with a more informational-analytical standpoint. The rationale of our research paper lies within the fact that very little research has been conducted in regards to ethical approaches towards the aspects of ransom dilemma phenomenon. Hence, with this research paper, we would like to fill in this research gap and bring in something new and interesting within the studies on ethics. Key words: Ransom dilemma, terrorists, ransom payment, consequentialism, deontology, quid pro quo.